The LPS Responsiveness in BN and LEW Rats and Its Severity Are Modulated by the Liver. (30th July 2018) - Fang, Haoshu; Jin, Hao; Hua, Chuanfeng; Liu, Anding; Song, Zichen; Chen, Xulin; Dirsch, Olaf; Dahmen, Uta
Abstract : Differences in LPS responsiveness influence the outcome of patients with sepsis. The intensity of the response is highly variable in patients and strain dependent in rodents. However, the role of the liver for initiating the LPS response remains ill defined. We hypothesize that hepatic LPS uptake is a key event for initiating the LPS response. In the present study, the severity of the LPS-induced inflammatory response and the hepatic LPS uptake was compared in two rat strains (Lewis (LEW) rats and Brown Norway (BN) rats). Using a transplantation model, we demonstrated the decisive role of the liver. The expression of hepatic TNF- α, IL-6, and IL-1 β mRNA levels in BN rats was significantly lower than that in LEW rats. LEW rats were sensitized to LPS via G-CSF pretreatment. Sensitization caused by G-CSF pretreatment induced severe liver injury and mortality in LEW rats, but not in BN rats (survival rate: 0% (LEW) versus 100% (BN), p < 0.01 ). LEW rats presented with higher liver enzymes, more alterations in histology, and higher expression of caspase 3 and higher cytokines levels. One of the reasons could be the increased hepatic LPS uptake, which was only observed in LEW but not in BN livers. Using the transplantation model revealed the decisive role of the LPS responsiveness of the liver. Injection of LPS to the high-responding LEW recipient before transplantation of a low-responder BN liver resulted in a 50% survival rate. In contrast, injecting the same dose of LPS into the high-responding LEW recipient after transplanting the low-responding BN liver resulted in a 100% survival rate. The severity of inflammatory response in different strains might be related to the differences in hepatic LPS uptake. This observation suggests that the liver plays a genetically defined decisive role in modulating the inflammatory severity.